Statistical models for chili productivity - Wijayanto, Hari; Sumertajaya, I. Made; Fitrianto, Anwar; Sri Wahyuni, (Hikari, 2014)
Horticulture is one of the important commodities in the agricultural sector. Developments of horticulture data collection have been conducting to improve planning. One of which is a method of Rumpun Counting (RC) to estimate productivity of horticultural commodities. However, the RC method is still facing difficulties in its application, for example the observation for commodity repetitive crop harvesting, such as chili. This study attempts to find out an appropriate statistical model among several alternatives for chili productivity in district Cianjur, West Java, Indonesia. We found that each group possesses a specific appropriate model.